Macrophage Biology and Mechanisms of Immune Suppression in Breast Cancer - Mehta, Anita K.; Kadel, Sapana; Townsend, Madeline G.; Oliwa, Madisson; Guerriero, Jennifer L. (Frontiers in Immunology, 2021)
Macrophages are crucial innate immune cells that maintain tissue homeostasis and defend against pathogens, however their infiltration into tumors has been associated with adverse outcomes. Tumor-associated macrophages (TAMs) represent a significant component of the inflammatory infiltrate in breast tumors and extensive infiltration of TAMs has been linked to poor prognosis in breast cancer. Here we detail how TAMs impede a productive tumor immunity cycle by limiting antigen presentation and reducing activation of cytotoxic T lymphocytes (CTLs) while simultaneously supporting tumor cell survival, angiogenesis, metastasis. There is an urgent need to overcome TAM-mediated immune suppression for durable anti-tumor immunity in breast cancer. To date, failure to fully characterize TAM biology and classify multiple subsets has hindered advancement in therapeutic targeting. In this regard, the complexity of TAMs has recently taken center stage owing to their subset diversity and tightly regulated molecular and metabolic phenotypes. Here we discuss reveal major gaps in our knowledge of the functional and phenotypic characterization of TAM subsets associated with breast cancer, before and after treatment. Future work to characterize TAM subsets, location and crosstalk with neighboring cells will be critical to counteract TAM pro-tumor functions and to identify novel TAM modulating strategies and combinations that are likely to enhance current therapies and overcome chemo- and immuno-therapy resistance.